2008
DOI: 10.1055/s-2008-1039654
|View full text |Cite
|
Sign up to set email alerts
|

Wieviel Bandscheibengewebe wird bei der perkutanen Nukleotomie tatsächlich entfernt?

Abstract: In an experimental study with standardized conditions nuclear material of 40 human lumbar discs was excised. In 20 the non-automated discectomy method was used (NAPLD-method). In the other 20 the automated discectomy method (APLD-method). The excised material was weighted. After the removal, the material of the NAPLD-method was wet with isotonic saline over 45 minutes and again weighted. Afterwards the wet material of both methods was freeze dried and again weighted. The weight of the wet material of the NAPLD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Results of this and other studies have shown that changes in disc biomechanics are affected by the amount of material removed 70,90,113,114 . Thus, to allow comparison of the masses removed using the different nuclectomy techniques, the excised wet mass needs to be converted to a dry mass, to remove the confounding variability due to disc hydration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of this and other studies have shown that changes in disc biomechanics are affected by the amount of material removed 70,90,113,114 . Thus, to allow comparison of the masses removed using the different nuclectomy techniques, the excised wet mass needs to be converted to a dry mass, to remove the confounding variability due to disc hydration.…”
Section: Discussionmentioning
confidence: 99%
“…Results of this and other studies have shown that changes in disc biomechanics are affected by the amount of material removed. 70 , 90 , 113 , 114 Thus, to allow comparison of the masses removed using the different nuclectomy techniques, the excised wet mass needs to be converted to a dry mass, to remove the confounding variability due to disc hydration. Furthermore, regardless of the technique used to achieve NP removal, clinical studies have not found a correlation between the amount of material removed and the long‐term outcomes of nuclectomy, thus the appropriate quantity of disc material to be removed is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Next, a cruciate incision was created in the posterolateral annulus using a #11 scalpel blade. Afterwards, either 2 or 4 mm pituitary rongeurs were used to remove 1.71±0.38 g of nuclear material, which is approximately 50% of NP volume (Castro et al, 1992; Dullerud et al, 1993). Amount of NP removed was not correlated with sample degeneration (r = 0.19, p = 0.5).…”
Section: Methodsmentioning
confidence: 99%